Beyond Sanctions: ECOWAS and the Resurgence of Military Coups in West Africa - Olubiyo, Kolade G.; Ayodele, Iyanu-Oluwa A. (ABUAD Journal of Social and Management Sciences, 2024)
The recent resurgence of military coup d’etat in the West African region is alarming and problematic because of its contagion effect. Since 2019, Chad, Mali, Guinea, Burkina Faso and Niger have experienced military coup d’etat. As part of the efforts aimed at reversing military coups in these States, ECOWAS’ swift response has been in the form of sanctions, which include economic blockade, movement restrictions for the coup leaders, severance of diplomatic relations, and suspension of military leaders from the international community, among others. This effort has neither deterred the coup leaders nor hastened the return to civil rule. This paper attempts to examine ECOWAS’ responsibility beyond the imposition of sanctions in the era of resurgent coups in West Africa. The paper adopts the qualitative method of data collection using secondary sources, which include published books, journals, resolutions, and proceedings of ECOWAS. The paper argues that while ECOWAS is performing its moral obligation by imposing sanctions, the organisation lacks the capacity to compel West African leaders in the entrenchment of good governance. It, however, concludes that ECOWAS needs to re-strategize by having a potent framework capable of deepening good governance and stability of democracy in West Africa.